The imperative of sustainable growth and reporting integration. The fourth era in the corporate reporting development - Karmańska, Anna (Copernican Journal of Finance & Accounting, 2014)
This article is aimed at the presentation of an opinion in the important discussion about the further development of corporate performance reporting standards, which go far beyond the standards of financial reporting. This text, which is the second part of a two-part analysis, refers to the problem of a new trend of corporate reporting primarily for two reasons: (1) to point to the legitimacy of the joint determination by economic sciences of the axis around which reporting on corporate (organisation) performance should revolve, (2) in view of the variety of perceptions of value, to make everybody aware that different elements of corporate reporting should be compatible and that its usefulness for a wide range of stakeholders is predetermined by the explicitness of perception of the categories which are present in these elements. The present article is also aimed at the presentation of a qualitative surge of corporate performance reporting which is being made as a result of the focus on these corporate aspects thanks to which – with the simultaneous imperative of sustainable growth – value is created. This is the reason for the emergence of the fourth era.